(3GdbhGfjfs - (3Gdbej, GdLjdGfj, GdejQRG Gdbej, CHh GdbGSe Hf eMeO MSjf, J (B1231 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3GdebUO GdKGfj aj GdCOdI GdYbdjI hGdeQGO HGdOdjd GdYbdj gh Mce Ybdj jJhUd Hg Ydi GdMce GdTQYj hjfJbd ef GdYde HGdMce GdYbdj Ydi GdYde HGdMce GdTQYj hgj CbSGe jPcQ aj Wj bhGfjf efgG HGdMce Hg (B....s
(3BNQgG (B:s
... (3ceG MbbfGg aj eMdg eSJaGO ef JJHY GdCNHGQ hJVGYja GdeSGFd GdTQYjI Ke Ef GdeQLMGJ aj GdCOdI GdeJYGQVI bO JJQcH hJNJda adG HO ef edGMXI GdeLehY hehGRfI HYVgG hGdJRGe GdQGLM hJQc GdeQLhMs
(3efShNI Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5/183s
(3EjVGM Gdecfhf (B2/244s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs